2022
DOI: 10.1126/sciadv.abl7263
|View full text |Cite
|
Sign up to set email alerts
|

BRN2 as a key gene drives the early primate telencephalon development

Abstract: Evolutionary mutations in primate-specific genes drove primate cortex expansion. However, whether conserved genes with previously unidentified functions also play a key role in primate brain expansion remains unknown. Here, we focus on BRN2 ( POU3F2 ), a gene encoding a neural transcription factor commonly expressed in both primates and mice. Compared to the limited effects on mouse brain development, BRN2 biallelic knockout in cynomolgus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…These findings were confirmed with immunofluorescent staining of human organoids of SATB2 (Figure 6C, <1.5% cells) and PSMB5 (Figure 6I, ∼10% of cells) across 8-weeks, 10.5-weeks, and 14-weeks differentiation time points corresponding to segments 7, 8, and 9, respectively (Figure 6C and 6I). Also, POU3F2 , encoding a transcription factor important for primate radial glia expansion and differentiation 47 , displayed no expression throughout organoids maturation by BOMA (Figure 6A), and indeed it was found expressing in a small number of cells (∼3%) in organoids by immunostaining (Figure 6F).…”
Section: Resultsmentioning
confidence: 99%
“…These findings were confirmed with immunofluorescent staining of human organoids of SATB2 (Figure 6C, <1.5% cells) and PSMB5 (Figure 6I, ∼10% of cells) across 8-weeks, 10.5-weeks, and 14-weeks differentiation time points corresponding to segments 7, 8, and 9, respectively (Figure 6C and 6I). Also, POU3F2 , encoding a transcription factor important for primate radial glia expansion and differentiation 47 , displayed no expression throughout organoids maturation by BOMA (Figure 6A), and indeed it was found expressing in a small number of cells (∼3%) in organoids by immunostaining (Figure 6F).…”
Section: Resultsmentioning
confidence: 99%
“…In BRN2KO monkeys, the neurogenic behavior of cortical progenitors is similarly altered as in Brn1/2-cKO mice 36 . To test if the mechanisms by which BRN1/2 regulate progenitor behavior are evolutionary conserved, we first inhibited BRN1/2 activity in wild-type ferrets at E35 by IUE with pCAG-Brn-DBD-EnR, a dominant negative inhibitor of BRN1/2 function (Fig.…”
Section: Brn1/2 Function Is Conserved Across Phylogenymentioning
confidence: 90%
“…While our findings provide evidence for an evolutionary conserved role for BRN1/2 regulation of transcriptional programs that control progenitor behavior, it remains to be established to what extent the function of these transcriptional regulators has been modified during brain evolution to produce differences in brain size. For example, disruption of BRN2 function alone affects cortical development in monkeys 36 , but not in mice 18,19 , suggesting that redundancy of BRN1 and BRN2 function is not universally conserved. In addition, recent studies have shown that during evolution, enhancers that control neuronal gene expression have been altered by mutations that affect predominantly binding sites for a limited set of transcription factors, including BRN1/2 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations